A contribution to the knowledge of Dryinidae of Argentina: descriptions of the hitherto unknown males of gonatopus argentinus olmi and trichogonatopus richardsi olmi (hymenoptera chrysidoidea) - Virla, Eduardo Gabriel (2010)
The males of Gonatopus argentinus Olmi and Trichogonatopus richardsi Olmi are described for the first time. In consequence of the discovery of its male, Gonatopus argentinus Olmi, 1986, in the past considered senior synonym of Gonatopus doellojuradoi (Ogloblin, 1938), is revalued and considered a good species. In consequence of the discovery of its male, Trichogonatopus richardsi Olmi is transferred from Trichogonatopus Kieffer, 1909, to Gonatopus Ljungh, 1810. Gonatopus richardsi (Olmi) new comb. is preoccupied by Plectrogonatopus (= Gonatopus) richardsi Moczar, 1965, so that Gonatopus trichosoma new name is proposed for G. richardsi (Olmi). The hosts of both above species are discovered: Spangbergiella vulnerata (Uhler) (Cicadellidae Deltocephalinae)for G. argentinus; Curtara pagina DeLong & Freytag (Cicadellidae Gyponinae) and Mendozellus asunctia Cheng (Cicadellidae Deltocephalinae), for G. trichosoma.Gonatopus argentinus Olmi and Trichogonatopus richardsi Olmi are described for the first time. In consequence of the discovery of its male, Gonatopus argentinus Olmi, 1986, in the past considered senior synonym of Gonatopus doellojuradoi (Ogloblin, 1938), is revalued and considered a good species. In consequence of the discovery of its male, Trichogonatopus richardsi Olmi is transferred from Trichogonatopus Kieffer, 1909, to Gonatopus Ljungh, 1810. Gonatopus richardsi (Olmi) new comb. is preoccupied by Plectrogonatopus (= Gonatopus) richardsi Moczar, 1965, so that Gonatopus trichosoma new name is proposed for G. richardsi (Olmi). The hosts of both above species are discovered: Spangbergiella vulnerata (Uhler) (Cicadellidae Deltocephalinae)for G. argentinus; Curtara pagina DeLong & Freytag (Cicadellidae Gyponinae) and Mendozellus asunctia Cheng (Cicadellidae Deltocephalinae), for G. trichosoma.